1988
DOI: 10.1002/anie.198802941
|View full text |Cite
|
Sign up to set email alerts
|

The Structures of 1H‐Cyclopropabenzene and Its 1,1‐Bis(triisopropylsilyl) Derivative

Abstract: the same type of structure (Fig. 2) for the anion 2 as mentioned above for the case of the molybdenum compounds. The oxygen atom bridges all three titanium atoms and each pair of Ti atoms is linked via a side-on coordinated disulfide unit. The Ti-Ti distances of 314 to 318 pm are markedly greater than the Mo-Mo distances in the molybdenum clusters-as to be expected for a Ti'" compound, [**I Hetero n-Systems, Part 15. This work was supported by the Deutsche Forschungsgemeinschaft and the Fonds der Chemischen 1n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Fully optimized MP2(fc)/6-31+G(d) structures for benzocyclopropene ( 5H ), benzocyclopropenyl anion ( 5 ), and the latters inversion transition state ( 5pl ) were computed, and the most important geometrical data are summarized in Table and is in reasonable agreement with the experimental X-ray data, although the C−C bonds are systematically too long by approximately 0.004 and 0.02 Å, respectively. Apparently, the diffuse sp functions, which are needed to adequately describe the geometry of anions, lead to a slightly poorer structure in this instance.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Fully optimized MP2(fc)/6-31+G(d) structures for benzocyclopropene ( 5H ), benzocyclopropenyl anion ( 5 ), and the latters inversion transition state ( 5pl ) were computed, and the most important geometrical data are summarized in Table and is in reasonable agreement with the experimental X-ray data, although the C−C bonds are systematically too long by approximately 0.004 and 0.02 Å, respectively. Apparently, the diffuse sp functions, which are needed to adequately describe the geometry of anions, lead to a slightly poorer structure in this instance.…”
Section: Resultsmentioning
confidence: 63%
“… a All distances are in angstroms and angles in degrees. X-ray crystal data are given in parentheses and are taken from ref . …”
Section: Methodsmentioning
confidence: 99%
“…The deformation of the benzene moiety in 10 has been discussed in terms of the Mills−Nixon effect . The MP2/6-31G* geometry (Figure ) readily reproduces the X-ray structure of 10 , with the calculated bond lengths uniformly longer by ∼0.02 Å. The annelated C−C bond and the adjacent bonds are shortened while the rest of the C−C bonds are elongated.…”
Section: Discussionmentioning
confidence: 91%
“…This postulate states that annelation of small rings onto benzene induces significant alternation of bond lengths of the six-membered ring because of strain associated with bond angle deformation. This concept, which was proposed when benzene was thought by many to be an equilibrating mixture of valence tautomers, has generally been dismissed on the basis of more recent experimental and computational work, however [18][19][20]. Fowler et al have computed ring current densities of benzene fused with several small-ring hydrocarbons, and have shown that fusion of benzene with one or more cyclobutadiene rings disrupts the benzene ring current, but no disruption in the benzene ring current is observed when only saturated small rings are fused [21].…”
Section: Introductionmentioning
confidence: 99%